Trialogue Meetings: Engaging Citizens and Fostering Communities of Wellbeing Through Collective Dialogue - Mac Gabhann, Liam; Dunne, Simon (Frontiers in Psychology, 2021)
Community-based participatory approaches are widely recognised as valuable methods for improving mental health and well-being by enabling a greater sense of liberty among participants, through the development of equitable policies and practices, which accommodate a range of diverse perspectives. One such approach, ‘Trialogue Meetings’, has been found to encourage disclosure and dialogue surrounding mental health, facilitate the growth and development of communities in relation to peoples experience of mental health difficulties, service provider and community response. Emerging in the 1990’s because of perceived and felt inequitable relations between people with lived experience of mental health difficulties, family members of people with mental health difficulties and professionals providing mental health service provision. This approach has been shown to successfully reduce stigma and discrimination and improve relations between stakeholders in community and mental health care settings. Trialogue Meetings incorporate Open Dialogue methods to allow multiple stakeholder groups to participate in conversations around a given topic and enable the creation of a common language and mutual understanding. Trialogue Meetings have added benefits of allowing individuals to express themselves better, gain a sense of relationality and community with others and address predetermined power hierarchies with prescribed responses to peoples experiences. In this perspective, we present an outline for Trialogue Meetings as a medium for enhancing wellbeing, providing a transformative empowering process for deliberate discursive practice and engaging citizens through sustained collective dialogue.